Body weight prediction model analysis based on the body size of female Sakub sheep in Brebes District, Indonesia - ZAENAB NURUL JANNAH; BAYU ANDRI ATMOKO; ALEK IBRAHIM; MUHAMMAD AINSYAR HARAHAP; PANJONO PANJONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Jannah ZN, Atmoko BA, Ibrahim A, Harahap MA, Panjono. 2023. Body weight prediction model analysis based on the body size of female Sakub sheep in Brebes District, Indonesia. Biodiversitas 24: 3657-3664. Calculation of body weight is one of the important factors in seeing the performance of sheep (Ovis aries), breeding stock selection, and livestock management, such as the basis for consideration of feeding, medicine dosage, slaughter time, and growth evaluation. However, in smallholder farms, the availability of scales is an obstacle, not to mention the inadequacy of the pens’ construction, making the weighing process more difficult. The present study was conducted to analyze correlation and regression models and determine the best and most accurate regression model for predicting the body weight of female Sakub sheep using body sizes. Data on 150 female Sakub sheep kept by smallholder farmers and raised intensively in Paguyangan and Sirampog District, Brebes District, Central Java, Indonesia, were obtained. The Body Weight (BW) of Sakub sheep was weighed, and their body sizes, including body length (BL), chest girth (CG), and shoulder height (SH) were measured. The correlation was calculated using the Pearson correlation, regression models were analyzed and determined using simple, multiple, and automatic linear regression methods. Pooled means of 36.21±12.31 kg for BW and 67.13±7.97, 82.51±10.47, and 65.76±6.24 cm for BL, CG, and SH, respectively, were obtained in the present study. The body size has a positive and high correlation with BW, BL has the highest correlation with BW, which is 0.810, followed by CG (0.807) and SH (0.782). Meanwhile, the correlation of body size combination between BL, CG, and WH has the highest value, 0.883, followed by BL and CG (0.875), between CG and SH (0.875). The best body size and the most accurate (77.40%) to predict BW of female Sakub sheep is the combination of the three BL+CG+SH with regression equation model BW = 67,004+0.589BL+0.453CG+0.399SH. Meanwhile, the prediction of BW with a single body size is BL with the regression equation BW = -47,658 + 1,249BL with an accuracy of 65.40%. This study concludes that body size, namely BL, CG, and SH, can be used to predict BW of female Sakub sheep, either single or in 2 or 3 combinations. The prediction model BW using a combination of 3 body sizes has the highest accuracy, followed by a combination of 2 body sizes (BL+CG), and the last is BL as a single predictor.